Entrepreneurial Skills in Career Transition Program among Students with Special Educational Needs (SEN) - Pit, Ramlan; Noah, Norasikin binti Mohamad; Nassir, Siti Nor Idayu binti Mohd; Razak, Nur Izrin Fatin binti Abd; Nor, Nor Atmam Nazihah binti Mohamad (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
With today’s increasingly challenging and growing transformation and technology within the world of education, the impact on the education system among students with special educational needs (SEN) with learning problems is no less great. Various initiatives have been set by the ministry for the benefit of students with special educational need's future, such as the expansion of students with special educational need's Career Transition Program. This study aims to discuss the application of entrepreneurial skills in Career Transition Program among students with special educational needs (SEN). This study uses a qualitative approach, which is a method of structured interviews, observations and document analysis. The study sample is a total of four special educational teachers who teach vocational subjects. The findings of this study show that there are four elements of entrepreneurial skills that are applied to students with special educational need, especially with learning disabilities, which are the skills to produce products, the skills to market products, the skills to do business and communicate and the skills to calculate costs. Most individuals with special needs can perform productively if given the knowledge and skills through an appropriate educational program.